COMPARISON OF IMAGING TECHNIQUES IN THE EARLY DIAGNOSIS OF SACROILIITIS* - Remzi Çevik; Kemal Nas; Ali Gür; Mustafa Özateş; Safinaz Ataoğlu; Ferda Erdoğan; A. Jale Saraç; Ömer Satıcı (Archives of Rheumatology, 2000)
Sacroiliitis is usually the first and main feature of seronegative spondyloarthropathies. But the sacroiliac joints present a problem to the diagnostician because of their deep seated location and lack of motion. This forces us to rely heavily on imaging modalities to diagnose diseases of this joint. Therefore, many imaging techniques such as computed tomography (CT); single photon emission computed tomography (SPECT) bone scanning, and magnetic resonance imaging (MRI) have been studied. In our study MRI was performed in 48 patients with clinical evidence of sacroiliitis. MRI findings were compared with those at CT and SPECT. Of these patients 35 had abnormal CT seans (73%), 36 had abnormal SPECT seans (75%), and 44 had abnormal MRI scans(91,6%). We concluded that MR imaging provide the best objective and complementary evidence of sacroiliitis in patients with clinical features of inflammatory spinal disease.